Effects of corruption risks on access to information resources: the question - Червякова, О. Б. (Problems of legality, 2015)
The article examines the impact of actual corruption risks in providing access to information resources. Defined objective and subjective factors contributing to the corruption risks and the ways of their reduction. Attention is focused on the need to strengthen state control over the implementation of the law on ensuring transparency in government, including through the creation (definition) special authority.